Electron paramagnetic resonance spectroscopy and first-principles calculations of Cr3+ doped KDP crystals. Issue 27 (23rd June 2022) - Wei, Liening; Li, Yang; Jiang, Xuanyu; Wu, Pengcheng; Zhao, Xian; Zhang, Lisong; Liu, Baoan; Chai, Xiangxu; Xu, Mingxia; Sun, Xun; Hong, Wei
Abstract : The behavior of the Cr 3+ centers in KDP:(CrNO3 )3 crystals is illustrated by an analysis of experimental and theoretical calculations. Abstract : The characteristics of potassium dihydrogen phosphate (KDP) crystals with Cr(NO3 )3 doping at the ∼10 ppm level were studied using the ultraviolet-visible (UV-vis) absorption spectrum, electron paramagnetic resonance spectroscopy (EPR), and first-principles calculations. According to the UV-vis absorption spectrum, there are three additional absorption peaks in the 200–800 nm regions on KDP:Cr(NO3 )3 crystals compared with undoped KDP crystals. The angular-dependence EPR spectra of a Cr 3+ paramagnetic centre of the KDP:Cr(NO3 )3 crystal were obtained at room temperature. The spin Hamiltonian parameters ( g and D tensors) of the Cr 3+ centre were extracted using a least-squares fitting code. The first-principles calculations show that the formation energy is the lowest when the Cr atom substitutes the K atom. In addition, the d–d orbital electron transition Cr 3+ ion may contribute to the two absorption peaks (451 nm and 650 nm) in the UV-vis absorption spectrum. Based on the experiments and theoretical calculations, it was inferred that in the KDP:Cr(NO3 )3 crystal, Cr atoms occupy an average position of K atoms, and the charge compensation is reached through two adjacent H vacancies to meet the electrical neutrality requirement.